2022
DOI: 10.1021/acs.langmuir.2c00604
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Experimental Error in the Mapping of Electrical Properties with Electrostatic Force Microscopy

Abstract: Electrostatic force microscopy (EFM) is an emergent, powerful technique for nanoscale detection of electrical properties such as permittivity and charge distribution. However, the surface irregularity of samples has been unfortunately overlooked in most EFM studies. Herein, we use a polymer nanocomposite dielectric (PND) as the showcase and demonstrate that the morphological discontinuity at the matrix/particle interface can lead to major discrepancies or even incorrect results in the EFM study. First, the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Recently, in the topic of interface detection by EFM, the influence of the morphology, polarization, and charge in the interfacial region on measurement was analyzed by FEM simulation (Figure f). Significant impact from the surface irregularities was confirmed­(Figure g,h), which is much greater than the impact from polarization and charge modification in the interface . Hence, it was suggested that the local interfacial polarization and charge detection based on SPM should be dealt with carefully, with more attention paid to the morphology of the sample and the uncertainty in the EFM, which has a major impact on the conclusions.…”
Section: Interface Study By Scanning Probe Microscopy-based Measurementmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, in the topic of interface detection by EFM, the influence of the morphology, polarization, and charge in the interfacial region on measurement was analyzed by FEM simulation (Figure f). Significant impact from the surface irregularities was confirmed­(Figure g,h), which is much greater than the impact from polarization and charge modification in the interface . Hence, it was suggested that the local interfacial polarization and charge detection based on SPM should be dealt with carefully, with more attention paid to the morphology of the sample and the uncertainty in the EFM, which has a major impact on the conclusions.…”
Section: Interface Study By Scanning Probe Microscopy-based Measurementmentioning
confidence: 94%
“…Significant impact from the surface irregularities was confirmed(Figure 13g,h), which is much greater than the impact from polarization and charge modification in the interface. 212 Hence, it was suggested that the local interfacial polarization and charge detection based on SPM should be dealt with carefully, with more attention paid to the morphology of the sample and the uncertainty in the EFM, which has a major impact on the conclusions. Besides the above-mentioned factors, SPM, a surface testing technique, has the inherent problem to peel off the surface effect.…”
Section: Spatial Resolution In the Detection Of Electrostaticmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 172 reported that electrostatic force microscopy (EFM) is an innovative technique to detect the electric performance and charge distribution of the interface at nanoscale, as shown in Fig. 16(d) and (e).…”
Section: Function Of Interfacementioning
confidence: 99%
“…171 (d) Potential of the system when the probe is above the particle, interface, and matrix. 172 (e) Calculated results of the electrical force and force gradient. 172 (f) Schematic diagram of charge/discharge by scanning probe microscopy, SPM topography and amplitude images of the cross-linked nanocomposite (N 2 C 15 ).…”
Section: Function Of Interfacementioning
confidence: 99%